The parts for the whole: parataxic mentality in Homer and the Old Testament (Revista Archai, 2018)
This article aims to demonstrate the existence of a parataxic mentality both in Homeric works and in the Old Testament, establishing a parallel to show that the body, as a living organic unit, which is shown through its parts that express not only the whole but also the individual. Therefore, there is a possible relationship between what Giovanni Reale understood as the “parataxic mentality” of Homeric poems, and what Hans Walter Wolff indicates as the “stereometric-synthetic thinking” of the Old Testament. By attesting this relation and similarity between the mentalities of the Old Testament and the Homeric works, it’s shown not only the importance of a comparative study but also a renewal of both the anthropological grammar of these texts and the history of the anthropological concepts in Ancient Greece and even in the Judeo-Christian tradition.